Correlation between COHb, HIF-1α levels, and smoking habits with physical fatigue in online motorcycle taxi drivers - Ade Dwi Lestari; Adrianus Kosasih; Novendy Novendy; Magdalena Wartono; Diana Samara Tjam (Indonesian Journal of Biomedicine and Clinical Sciences, 2026)
Online motorcycle taxi drivers have varying working hours and rest periods which can influence the occurrence of fatigue among them. Additionally, working on the road made them exposed to air pollution, including carbon monoxide. Several studies have reported a relationship between carbon monoxide and fatigue levels in specific types of occupations. Therefore, the aim of this study is to determine the correlation between smoking habits, occupational factors, carboxyhemoglobin (COHb) levels, and work fatigue, as well as the correlation between hypoxia inducible factor 1-alpha (HIF-1α) and COHb levels. Demographic characteristics, smoking habits, and occupational factors were measured using a questionnaire. COHb and HIF-1α levels were measured through blood biomarker examinations, while fatigue levels were assessed using the IFRC questionnaire. Data analysis was conducted using Spearman correlation tests in the SPSS program. The results showed that majority of respondents were male (87%), with the highest age range being 19-44 yr (85.5%). More than 50% of respondents were classified as overweight or obese. The majority of them were light smokers (78.3%). Most respondents had normal COHb levels, and in terms of fatigue levels, a larger proportion experienced mild fatigue (66.7%). No correlation between COHb levels, smoking habits, occupational factors, and fatigue levels as well as between HIF-1α and COHb levels (p>0.05). In conclusion, no correlation is found between COHb levels, smoking habits, occupational factors, and fatigue levels. Similarly, there is no correlation between HIF-1α and COHb levels.